Batch and bulk adsorptive removal of anionic dye using metal/halide-free ordered mesoporous carbon as adsorbent. (25th October 2021) - Mittal, Jyoti; Mariyam, Asna; Sakina, Farzeen; Baker, Richard T.; Sharma, Ashok K.; Mittal, Alok
Abstract: The present report is an outcome of investigations to assess the adsorptive potential of a synthesized metal- and halide-free variant of ordered mesoporous carbon (OMC) towards an anionic azo dye, Methyl Orange. The results of preliminary studies, carried out in batch mode, helped in setting up the process variables to achieve optimum adsorption conditions. The experimental data were then fitted to Langmuir, Freundlich, Temkin, and Dubinin-Radushkevitch isotherm models. The equilibrium data fitted well to the Langmuir model at 303 K and the monolayer adsorption capacity was 0.33 mmol g −1 . The adsorption kinetics were explored by fitting the data to pseudo-first-order and pseudo-second-order kinetic models. The latter described the kinetics well, as indicated by higher regression coefficients. To elucidate the mechanism of mass transfer, various well-known mathematical models were employed. The adsorption of the dye was found to involve particle diffusion. Thermodynamic studies revealed that the adsorptive uptake of Methyl Orange by the OMC was spontaneous (ΔG 0  = −23.71 kJ mol −1 ) and exergonic (ΔH 0  = −123.15 kJ mol −1 ). Finally, the bulk removal of the anionic dye was investigated through column operations followed by column regeneration (desorption) studies. Column saturation of up to 96.55% could be realized. Values for dye recovery reached up to 93.26%. The column efficiency was then evaluated by carrying out three consecutive adsorption/desorption cycles. The results obtained indicated that the adsorbent has a good ability to eliminate Methyl Orange from wastewater, both in batch and column operations. Graphical abstract: Image 1 Highlights: Synthesis of metal- and halide-free variant of ordered mesoporous carbon (OMC). Full analysis of the OMC using imaging, diffraction and spectroscopic methods. Batch and bulk removal of Methyl Orange with >98% efficiency using OMC. Efficient regeneration of exhausted fixed-bed column of OMC using 2-methoxy ethanol.